Celebrating Teachers’ Day - MISHRA, VANDANA (THE PRIMARY TEACHER, 2014)
A jewel in the treasure of India, Dr. Radhakrishnan was born in a remote village near Madras. He emerged as a spark from the masses and achieved great heights leaving remarkable footprints as a student, teacher and politician. His creative mind and style of speech played a major contribution in his success. He was a great teacher of humanity who gave message of humanity to the masses through his valuable writings and speeches. He can be marked honestly as a genuine representative of India. His views on education and vision of human destiny will always be appreciated all over the world. A remarkable theme is always seen in his speeches that made his audience speechless or spell bound. His birthday in our country is celebrated as “Teachers’ Day” on 5th September. This paper is a tribute to the great soul with a focus on some of his contributions. This paper includes some parts of his life, philosophy and his vision for education that proves him- a great teacher.